A new species of Otothyropsis (Siluriformes: Loricariidae) from the upper Río Paraná basin, Paraguay, with a discussion of the limits between Otothyropsis and Hisonotus - Calegari, Bárbara B.; Morlis, Walter Gill; Reis, Roberto E. (Zootaxa, 2017)
Otothyropsis dialeukos is described from Itá creek, tributary to the upper Río Paraná basin, Paraguay. The new species is distinguished from its congeners by having a unique caudal-fin coloration pattern composed of a brown to almost black background with roundish hyaline blotches in the middle of the outermost branched rays and a hyaline posterior border interrupted in middle rays; abdomen entirely covered by enlarged plates, without naked areas; longer pectoral- and dorsal-fin spines; absence of a raised crest of enlarged odontodes on the posterior portion of the parieto-supraoccipital, and other morphometric and meristic features. Morphological traits and geographic distributions of all species of Otothyropsis and Hisonotus are analyzed and a discussion on the limits between those genera is presented.